Educational Computer Game and Their Implications on Early Children's Language Skill - Eti Nurhayati; Inayah El Fitri; Durtam Durtam; Jazariyah Jazariyah (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2022)
Language is an important comunication tool for everyone, including for early childhood. With language, early childhood can express feelings, thoughts, share experiences and knowledge, and socialize. Therefore language skills need to be developed, especially tor early childhood. This research aims to determine the language development of early childhood through educational computer games at school, how the effect of educational computer games on the language skills for early childhood. This study is a pre-experimental method with the one group pretest-posttest design. The results showed that 56 % of early childhood language skills are influenced by educational computer games, while the remaining 44 % were influenced by other factors that were not the focus of this study, then there is a significant positive effect on language skills based on the educational computer games coefficient value (X) on language skills (Y) of 0.730 which indicates the direction of positive influence and based on the t-test, the results of tcount = 11.179 2.039 = ttable. Based on the results of the analysis, it can be concluded that there is an influence of educational computer games on early childhood language skills.